(untitled) (Світ фінансів, 2017)
Ткаченко Н. В. Проблеми та перспективи розвитку професійних перестраховиків в Україні. Розглянуто необхідність розвитку професійного ринку перестрахування в Україні. Висвітлено проблеми та перспективи подальшого створення інституту професійних перестраховиків. Визначено основні принципи створення національної перестрахувальної компанії. Tkachenko N. Problems and prospects of professional reinsurers development in Ukraine. The necessity of professional reinsurance market in Ukraine is considered. Problems and prospects of the further creation of professional reinsurers institute are explained. The fundamental principles of national reinsurance company creation are determined.